2005
DOI: 10.1038/sj.onc.1208443
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ1/Smad3 counteracts BRCA1-dependent repair of DNA damage

Abstract: Inactivation of the BRCA1 gene has been found to confer susceptibility to early-onset familial breast and ovarian cancers. BRCA1 regulates DNA repair, chromatin remodeling and affects gene transcription. Transforming growth factor-b (TGFb) is a potent regulator of growth, apoptosis and invasiveness of tumor cells, including breast cancer cells. Here we show that Smad3 which is a component of the TGFb signaling pathway, forms a complex with BRCA1 in vitro and in vivo. The interaction is mediated by the MH1 doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 30 publications
4
43
0
Order By: Relevance
“…Additionally, increased TGF-β1/Smad3 in HN-Smad4 -/-tissues could contribute to downregulation of the Fanc/Brca pathway. In support of the latter hypothesis, Smad3 has been shown to bind to the Brca1 protein and inhibit Brca1 nuclear foci formation and DNA repair efficiency (49). Thus, genomic instability coupled with hyperproliferation and reduced apoptosis may allow HN-Smad4 -/-cells to escape from DNA damage-induced cell death during tumorigenesis.…”
Section: Figurementioning
confidence: 68%
“…Additionally, increased TGF-β1/Smad3 in HN-Smad4 -/-tissues could contribute to downregulation of the Fanc/Brca pathway. In support of the latter hypothesis, Smad3 has been shown to bind to the Brca1 protein and inhibit Brca1 nuclear foci formation and DNA repair efficiency (49). Thus, genomic instability coupled with hyperproliferation and reduced apoptosis may allow HN-Smad4 -/-cells to escape from DNA damage-induced cell death during tumorigenesis.…”
Section: Figurementioning
confidence: 68%
“…Although these data refer to a situation without irradiation, they might be comparable to our 16-h TGF-b1 preincubation. In addition, it has been shown that TGF-b1 via SMAD3 counteracts BRCA1-dependent DNA repair (35), thus supporting an effect of TGF-b1 impairing DNA integrity. However, several days after irradiation, reduced numbers of cells harboring chromosomal aberrations were noticed in the presence of TGF-b1 (14).…”
Section: Discussionmentioning
confidence: 97%
“…However, it is unclear at this stage as to the functional role of the BRCA1 and/or BRCA2 associated irradiation [29][30][31], suggesting an alternative mode of activity for many of the candidate modifier genes.…”
Section: Discussionmentioning
confidence: 97%